Lima Belas Tahun Penelitian Kualitas Laporan Keuangan Indonesia: TOPIK, METODE, DAN TEORI - Yuni Rimawati; Tito IM. Rahman Hakim; Faradila Yuliana Putri (Politeknik Caltex Riau, 2025)
Main Findings: This study aims to provide an overview of the development of research on financial report quality in Indonesia over the past 15 years, using articles indexed in Sinta 1-6. This study found articles on the quality of private and public sector financial reports. Research Methodology: This study employed a systematic literature review. This study mapped the research topics, methods, populations, and theories across 115 articles. Theoretical and Policy Implications: The results of the analysis can provide an overview of potential future research and a picture of the state of financial report quality in Indonesia. Research Novelty - Mapping into four classifications: research topic, research method, research population, and research theory, using articles indexed in Sinta Indexes 1 to 6 on the topic of financial report quality, with an observation period of 2010-2024.